Fan Engagement Through Multilingual Code Practices in SEVENTEEN’s X - Dewi Lestari Pambudi; Lina Purwaning Hartanti (Universitas Muhammadiyah Mataram, 2026)
This study examines fan engagement through multilingual code practices in SEVENTEEN’s official X posts within digital fandom spaces. Using Social Presence Theory (Short et al., 1976), this study analyzes eight official posts uploaded on SEVENTEEN’s X account (@pledis_17) and 400 fan comments collected from the corresponding comment sections through a qualitative descriptive approach. The findings reveal that SEVENTEEN’s official posts predominantly employ immediacy as the primary engagement strategy, while intimacy emerges as the most dominant form of fan engagement in the comment sections. In terms of language use, English is the dominant language in fan responses, followed by mixed-language and other-language comments, indicating active multilingual participation among global fans. These findings suggest that multilingual code practices not only facilitate information dissemination but also encourage emotional interaction and audience participation. Overall, multilingual communication functions not only as a strategic communication practice but also as a mechanism for fostering fan engagement and strengthening digital fandom communities.